Brainstem cavernomas: a 10-case surgical series - Romero Vinet, Hugo; Baldoncini, Matias; Campero, Álvaro (Revista Argentina de Neurocirugía, 2026)
Introduction: brainstem cavernomas are low-flow vascular malformations with a high risk of bleeding and significant neurological morbidity. Their surgical management remains challenging due to their location in eloquent brain areas.Objectives: to present our surgical series of brainstem cavernomas, analyze clinical and imaging outcomes, as well as the approaches used according to their location.Methods: we conducted a retrospective review of 10 consecutive patients who underwent surgery for brainstem cavernomas between January 2021 and February 2025. Clinical, radiological, surgical, and postoperative outcomes were analyzed.Results: 6 patients were female; mean age was 39 years. All had prior hemorrhage. Lesions were in the pons (50%), medulla (30%), and midbrain (20%). Surgical approaches were chosen based on lesion location, using suboccipital or extended retrosigmoid routes. Complete resection was achieved in all cases. Six patients fully recovered; 2 had transient neurological deficits. No new permanent sequel was reported.Conclusion: microsurgical resection of brainstem cavernomas is feasible and safe in experienced centers, with favorable outcomes in most selected cases. Risk stratification tools, such as the Lawton grading scale, support optimal surgical decision-making.
Keywords: Brainstem; Cavernous malformation; Posterior fossa; Retrosigmoid